The development of responsible & sustainable business practice: value, mind-sets, business-models - Painter-Morland, Mollie; Hibbert, Sally; Cooper, Tim (Springer, 2018)
The main goal of this Special Issue (SI) of the Journal of Business Ethics is to explore the changes in values and mind-sets that are required for new, sustainable and ethical business models and consumption practices to flourish. Notable manifestations of efforts to embody an ethical perspective within business practices are seen in recent attempts to rethink business models (Bocken, Short, Rana and Evans, 2014, Linder and Williander, 2015) and to develop hybrid organisations (e.g., social enterprises) and collaborations (Defourney and Nissens, 2006) more likely to balance economic, social and environmental needs. Changes in consumption range from selecting more ethical and sustainable options, e.g., fair trade, renewable energy etc. (De Pelsmacker and Janssens, 2007; Bang, Ellinger, Hadjimarcou and Traichal, 2000) and slowing the acquisition and replacement of goods (Cooper, 2005, 2010) to more radical shifts in lifestyles such as voluntary simplicity (Marchand, Walker and Cooper, 2010; Shaw and Riach, 2011). It is widely recognised that embedded practices and beliefs constrain change, but there is a keenness to investigate the emergence of business and consumption practices that shift away from traditional resource-depleting forms of capitalism. We are delighted to guest edit this special issue and present a set of papers that illustrates the appetite to generate this insight by examining diverse forms of enterprise and consumption, evidencing efforts to embed more ethical and sustainable approaches. Though the papers vary in the conceptual lenses that they adopt, the trend towards a process-based perspective of valuation is evident among them. Hence we start our editorial by articulating some of the changing conceptions of value and the potential to explore how evolving mind-sets and mental models can influence responsible and sustainable business.